Work Culture of Sundanese Transmigrant Community Sindangkasih Village Ranomeeto Barat District Konawe Selatan Regency - muhamad turmudi (International Journal of Nusantara Islam, 2020)
This article provides an overview of the work culture of the Sundanese transmigrant community in Sindangkasih Village. Sindangkasih is a village located in the District of Ranomeeto Barat Barat, Konawe Selatan Regency opened as a residential area in 1968 through a transmigration program. The first generation of Sindangkasih Village community originated from the transmigration group came from several districts in West Java including Ciamis Regency, Tasik Malaya Regency, Garut Regency, Sumedang Regency, Majalengka Regency, Cirebon Regency, Kuningan Regency and Bandung Regency.Using qualitative methods this article finds that (1) the first generation of Sindangkasih Village people came from West Java with Sundanese ethnicity who joined transmigration in 1968 generally working as farmers (2) the next generation besides continuing to work as farmers, the people of Sindangkasih Village have chosen the profession as traders, builders, mechanics, car rental, barbershop and rice mill (3) the work culture formed from the efforts of the Sindangkasih village community is discipline, skillful, creative, openness and cooperation.